Pengukuran Kinerja Keuangan Bank Panin Dubai Syariah Menggunakan Economic Value Added Dan Financial Value Added - Aisyah, Siti; Ritonga, Indah Lestari; Harmain, Hendra (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2023)
The study aims to determine the financial performance of PT Bank Panin Dubai Syariah (PNBS) for the 2017-2021 period which was analyzed using Economic value Added (EVA) and Financial Value Added (FVA) approaches.This study used a qualitative descriptive research approach using secondary data. The data used are PNBS in 2017 succeeded in creating economic value added and financial value added by minimizing bank expenses and maximazing bank added value, which means that the EVA and FVA values in that period are worth positive. However, in 2018, 2019, 2020 and 2021 PNBS cannot create economic value added and financial value added value because PNBS cannot maximize added value and minimize bank expenses, which means that the EVA and FVA values in that period are negative. Thus it can be concluded that using the EVA and FVA approaches in calculating bank financial performance more effective because the EVA and FVA approaches cosider the cost of capital or the cost of capital.